The Wealth Effect of the Securities Commission and the Central Bank Announcement - Yu, Kee Su (1997)
This study examined the effect of events announcement by The Securities Commission and The Central Bank on the Kuala Lumpur Stock Exchange Composite Index and Sectoral Indices. The data and information on the event announced and market index was obtained from the Kuala Lumpur Stock Exchange Library, newspaper reports, etc. The period of study was from March 1, 1993 to August 31, 1997 for The Securities Commission event announcement, whereas for The Central Bank Event announcement, the period was from January 1, 1994 to February 28, 1994. An event study method was employed to estimate the market return and average return. The statistical significance of the average return were ascertained at 5 percent level. A sample of 16 events for The Securities Commission and a sample of 7 events for The Central Bank were analyzed. The findings showed that there was no evidence of significant abnormal returns due to the events announced by The Securities Commission. This implies that events announced by The Securities Commission are of non-event and no 'news' to the market (Composite Index). F or the events announcement by The Central Bank, the finding showed some evidence of significant average returns both on the Composite Index and Sectoral Index (Finance Sector). This means the event announcement by The Central Bank are considered 'news' to the market.An interesting point to note is that, The Central Bank's announcement were leaked to the market a week before the announcement. In conclusion, though the general events announcement by the authority were no 'news' to the market, the specific event announcement by the authority are considered 'news' to the market and market will react accordingly towards the information content of such specific event announcement. An interesting point noted was the leakage of early information prior to the event announcement.